Efficiency of a self-organizing Ising model of financial markets - Antenorcruz, Jude Maria V. (Animo Repository, 2023)
Individual agents in financial markets decide based on market conditions, external news and information, and personal idiosyncrasies; from the collective action of such agents arise the unpredictable market dynamics. These actions affect the overall efficiency of the market, which measures how well the price reflects the available incoming information. Here, we implement the self-organizing Ising model of Zhou and Sornette (2017) to probe the efficiency of simulated financial markets under various conditions. Efficiency is parametrized by the dispersion of the generalized Hurst exponents obtained from multifractal detrended fluctuation analysis. Scanning different model parameters sets reveal the regimes of highest efficiency in simulated markets.